A STUDY TO ASSESS THE EFFECTIVENESS OF PLANNED TEACHING PROGRAMME (PTP) ONKNOWLEDGE REGARDING BLOOD DONATION AMONG NON-PROESSIONAL COLLEGE STUDENTS IN SELECTED AREAS IN JAIPUR CITY (International Journal of Food and Nutritional Sciences, 2022)
Health care professionals including doctors, nurses and paramedical staffs are the guardians of the community. It is the duty of the entire health care establishments to ensure speedy recovery of their patients by providing quality health care. On day 1st, informed written consent was obtained from each sample after explaining the purpose of the study and was given assurance for keeping the information confidential. A pre-test was conducted by administering structured questionnaire, and then it was followed by administering Planned Teaching programme on blood donation among non professional student. The pre-test was Administered for student. On the 15th day a post- test was administered by using the same tool which was used in the pre-test. The findings of the study reveal that the mean differences of the pre-test and post-test which is statistically significant at .05 levels. Hence it indicates a significant difference and effectiveness of planned teaching programme in terms of knowledge gain by the non professional students.